1966
DOI: 10.1113/jphysiol.1966.sp007883
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of ions in the smooth muscle of the guinea‐pig taenia coli

Abstract: SUMMARY1. Tracer movements and ionic composition have been observed in the smooth muscle of the guinea-pig taenia coil in vitro at 4, and 350 C. The muscle was quiescent at 40 C, and did not show spontaneous electrical nor mechanical activity for 25 min after re-warming. It was therefore possible to make observations on the quiescent tissue at 350 C.2. The rate of loss of tracer sodium was sensitive to changes of temperature, with an average Qlo of 3-4 + 0-4 on warming in the range 4-350 C.Exponential analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

1966
1966
1979
1979

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 27 publications
6
35
0
Order By: Relevance
“…Figure la shows the same results as in Fig. la present in the slow phase (Buck & Goodford, 1966 (Goodford, 1962). It was found that adrenaline again increased the loss of 24Na significantly.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Figure la shows the same results as in Fig. la present in the slow phase (Buck & Goodford, 1966 (Goodford, 1962). It was found that adrenaline again increased the loss of 24Na significantly.…”
Section: Resultssupporting
confidence: 75%
“…4) instead of the curve normally found. It has been suggested that the curvature normally observed is due to an inhomogeneous distribution of potassium in the tissue (Goodford & Hermansen, 1961;Bauer et al, 1963;Buck & Goodford, 1966), and the present observations might indicate that more of the tissue potassium is exchangeable in the presence of adrenaline than under control conditions. They might alternatively be due to a changed ratio of cell volume to cell surface area, as has previously been observed by Freeman-Narrod & Goodford (1962).…”
Section: "K-uptakementioning
confidence: 51%
See 1 more Smart Citation
“…This result might suggest that the determination of the membrane potential is independent of Cl permeability. It has often been assumed that C1 in smooth muscle of the taenia col is distributed passively across the cell membrane (Buck & Goodford, 1966). On the other hand, some evidence against a passive distribution of Cl has been proposed (Casteels & Kuriyama, 1966;Casteels, 1969Casteels, , 1971.…”
Section: Discussionmentioning
confidence: 99%
“…The low cytoplasmic concentration of sodium (37.5 mM, Buck & Goodford, 1966) would therefore be at equilibrium across the curved vesicular surface with some 900 mM-Na, which exceeds the extracellular concentration of 137 mM-Na. Since many vesicles are observed to have openings into the extracellular fluid, the sodium might finally escape from the cells by this route.…”
mentioning
confidence: 99%